(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2022)
The Psychological Care of Infants and Children (Watson & Watson, 1928) was the first Behaviorism book translated into Brazilian Portuguese, published in the country in 1934 and 1941. In this article, we present a historical analysis of the emergence context of this translation and some characteristics of the translated text. Social conditions responsible for the development of child care, changes in the Brazilian publishing market resulting from the crisis of 1929, and the establishment of a culture of parent education seem to have promoted investment in the translation of the book and its dissemination in the country. This translation occupies a privileged position for disseminating behaviorism in Brazil. However, problems with the translation and critical evaluations of the preface, along with translation notes, seem to have delivered a less behaviorist book than its original, compromising its potential to disseminate behaviorism.